1985
DOI: 10.1121/1.392918
|View full text |Cite
|
Sign up to set email alerts
|

The effect of segmental and suprasegmental corrections on the intelligibility of deaf speech

Abstract: Three experiments were conducted to study the effect of segmental and suprasegmental corrections on the intelligibility and judged quality of deaf speech. By means of digital signal processing techniques, including LPC analysis, transformations of separate speech sounds, temporal structure, and intonation were carried out on 30 Dutch sentences spoken by ten deaf children. The transformed sentences were tested for intelligibility and acceptability by presenting them to inexperienced listeners. In experiment 1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 11 publications
3
20
0
Order By: Relevance
“…Findings from the present study suggest that it is the combined effects of segmental and suprasegmental impairments that lead to errors in vowel identifi cation as listeners are forced to adjust the weight of cues in the acoustic signal to optimize their perceptual strategies. Similar fi ndings have been observed in the speech of people who are deaf [21][22][23]45] . For highly intelligible speakers in the CG, on the other hand, acoustic characteristics of each vowel category were distinct and F0 was likely a redundant cue, therefore, manipulation of F0 did not affect the accuracy of vowel identifi cation.…”
Section: Vowel Identifi Cationsupporting
confidence: 74%
See 1 more Smart Citation
“…Findings from the present study suggest that it is the combined effects of segmental and suprasegmental impairments that lead to errors in vowel identifi cation as listeners are forced to adjust the weight of cues in the acoustic signal to optimize their perceptual strategies. Similar fi ndings have been observed in the speech of people who are deaf [21][22][23]45] . For highly intelligible speakers in the CG, on the other hand, acoustic characteristics of each vowel category were distinct and F0 was likely a redundant cue, therefore, manipulation of F0 did not affect the accuracy of vowel identifi cation.…”
Section: Vowel Identifi Cationsupporting
confidence: 74%
“…Computer-implemented improvements in F0 contours for speakers with hearing impairments have been correlated with signifi cant improvements in speech intelligibility scores [21][22][23] . Osberger and Levitt [23] report that the extent to which intelligibility was altered as a result of suprasegmental modifi cations was directly related to the frequency of segmental errors, particularly vowel segments.…”
mentioning
confidence: 99%
“…Subsequently formants were extracted with LPC-analysis and root-solving procedure using the ILS programming package (ILS, 1978). Next, the signal was resynthesized, applying a pitch synchronous energy correction (Maassen and Povel, 1985). Because plosives and vocal murmur deteriorate after resynthesis from formants, /ak/ was resynthesized from reflection coefficients, and the /b/ plus vocal murmur of the original spoken /bak/ was spliced in initial position in the resynthesized /bak/.…”
Section: Cvc Syllable Identification and Discrimination; Synthetic Spmentioning
confidence: 99%
“…Anderson-Hsieh, Johnson and Koehler (1992) used correlational methods and pronunciation ratings given to 60 non-native speakers, and also concluded that prosody makes a bigger contribution to accentedness than segments. Tajima, Port and Dalby (1997), Maassen and Povel (1985), Ulbrich and Mennen (2015) and Sereno, Lammers and Jongmann (2014), on the other hand, carried out a series of experiments and determined a much larger contribution of segmental features to foreign accent compared to suprasegmentals.…”
Section: Contribution Of Segments and Prosody To Foreign Accentmentioning
confidence: 99%